Evaluasi Tahapan Pemilihan Kepala Daerah Tahun 2024 di Kecamatan Sejangkung - Syamsiah, Nur; Radimin (Belalek, 2025)
This community service program (PKM) aims to analyze the implementation of the 2024 local elections in Sejangkung District. The activity was conducted in the form of a coordination meeting involving election organizers at the district level (District Election Committee) and at the village level (Polling Station Committees), as well as the Sub-District Leadership Coordination Forum (Forkopimcam) of Sejangkung District. This study was carried out due to the low level of voter participation in Sejangkung District during the 2024 local elections. The results of the analysis show that, in general, the stages of the election were implemented in accordance with the applicable regulations. However, voter participation remained low due to several factors, namely: a large number of voters residing outside the area, geographical conditions, low levels of political education and voter apathy, a reduction in the number of polling stations and invitations, and the influence of social media campaigns.